Revenge In Colombiana Movie (2011) Directed By Olivier Megaton: A Psychoanalytic Approach - Pradana, Agus Setya (2012)
In Colombiana movie the major problem of this study is how revenge is reflected in the major character's personality. The aim of this study is to analyze Olivier Megaton's the structural elements and the development of personality of the major character based on Psychoanalytic Approach. This study focuses on major character, namely Catalea. The benefit of this research is to give addition information which can be used by other literature researchers who are interested in analyzing this movie. This study uses two data sources, namely primary and secondary data source. The primary data source is the play script itself, while the secondary data are taken some information needed. The method of data collection is qualitative method. Based on the analysis, the study of this research comes from the major character problem. The problem itself is after she knows her parents are killed by the gangster; she has a desire to follows her purpose. The purpose itself is realized by doing revenge and killing the gangster who destroyed her family.